Unveiling the Impact of Solid Waste Management on Health and Poverty Alleviation in Dhaka City (Global Journal of Human-Social Science, 2023)
Dhaka the capital of Bangladesh faces significant challenges in solid waste management This study aims to unlock the transformative power of proper solid waste management SWM in improving the health and economic well-being of disadvantaged urban residents in the city While previous literature has focused primarily on waste collection disposal and recycling this study explores waste management as a powerful catalyst for poverty alleviation unlocking the untapped potential for transformative change Through qualitative and quantitative methods including surveys expert interviews and a systematic literature review the study identifies sources of pollution and factors affecting slum dwellers health and human development indicators It classifies conditions affecting the health-based vitality of slum dwellers The paper highlights the potential of sustainable waste management practices to improve health outcomes reduce disease incidence and alleviate poverty It emphasizes the need for policymakers to prioritize comprehensive waste management initiatives and promote community awareness and participation to address these issues
Keywords: urbanisation; slum population; solid waste; health hazard; poverty alleviation; human development